Zur Schadwirkung der Zikade Empoasca kraemeri (Ross und Moore) an Bohne (Phaseolus vulgaris L.). - Heyer, Wolfgang; Sternkopf, Günther; Chiang Lok, Maria Luisa; Cruz, Bienvenido (Contributions to Entomology = Beiträge zur Entomologie, 1989)
The cicada Empoasca kraemeri (Ross und Moore) is a serious pest on beans (Phaseolus vulgaris L.) in the Central American region including the southern states of the United States and the Caribbean. Its influence on the yield of seed depends on the density of the pest population and the time of the peak of the cicada population. These correlations are demonstrated at regression models. The protein content of the bean seeds was not negatively affected even by a strong attack. On the basis of the established relations of infestation and damage and of the population dynamics of the pest the following index figures for control measures were suggested: 14,8-21.2 individuals per 100 leaves at the hatching of the first generation of the cicadas and the first fully opened pinna of the plant, and 17,7-23,1 individuals per 100 leaves at the hatching of the second generation of cicadas and 9 pinnas per plant.